Analysis of Policy Implementation on The Duties and Functions of the Cabinet Secretariat (Case Study: Function of Policy Recommendation) - Johan Kurniawan; Roy Valiant Salomo (Publik : (Jurnal Ilmu Administrasi), 2021)
The implementation of the duties and functions of government institutions in the President's closest circle is an interesting thing to research. Its strategic position does not necessarily make its role carried out optimally. This can be seen from the function of providing policy recommendations carried out by the Cabinet Secretariat. Problems such as the disobedience of stakeholders to the flow of policy submissions, as well as problems on administrative matters such as supporting rules, communication strategies, information technology support, the effectiveness of policy monitoring, and the implementation of sanctions, have made the implementation of such functions not run optimally. Therefore, this study aims to analyze the implementation of the function of providing policy recommendations by the Cabinet Secretariat. The analytical framework used in this study is Policy Implementation Theory, particularly the Administrative Implementation Model by Matland (1995). This research uses the qualitative method that is descriptive analysis, with the focus of the research is the Cabinet Secretariat in the period 2015 until now. The result of this study is the implementation of the function of providing policy recommendations in dealing with various challenges and problems. However, improvement efforts have been made so that the performance of the function of providing policy recommendations, which is the main performance of the Cabinet Secretariat, can be more optimal.